2010
DOI: 10.1103/physreva.81.022718
|View full text |Cite
|
Sign up to set email alerts
|

Nonperturbative treatment of single ionization ofH2by fast highly-charged-ion impact

Abstract: We present a detailed analysis of the interference effects observed for ionization in collisions of fast highly charged projectiles with molecular hydrogen. We propose a nonperturbative semiclassical approach to describe the process under consideration by solving the time-dependent Schrödinger equation fully numerically on a 3D spatial grid. We present results for Kr 34+ -H 2 collisions at 63 MeV/u impact energy and discuss different structures observed experimentally in doubly differential cross sections. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Moreover, it has been reported that doubling frequency oscillations are not found in DDCS when a non-perturbative semiclassical approach to solve the TDSE fully numerically is used (see e.g. [30]).…”
Section: The Case Of Dielectronic Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been reported that doubling frequency oscillations are not found in DDCS when a non-perturbative semiclassical approach to solve the TDSE fully numerically is used (see e.g. [30]).…”
Section: The Case Of Dielectronic Moleculesmentioning
confidence: 99%
“…On the other hand, non-perturbative models, mainly based on the solution of the time-dependent Schrödinger equation (TDSE) for the active electron combined with a semiclassical scheme for the incoming projectile, were also developed (see e.g. [29,30]).…”
Section: Ion Beam Projectilesmentioning
confidence: 99%